Ecologically sustainable cassava plant protection (ESCaPP): a model for environmentally sound pest management in Africa - Yaninek, John S.; James, B.; Bieler, P. (1994)
Integrating the management of cassava pests into a strategy which meets the needs of individual farmers requires a conceptual framework for development and implementation. The Ecologically Sustainable Cassava Plant Protection (ESCaPP) project which began in 1993 in West Africa provides such a working model. ESCaPP is a regional project to develop, test and adapt sustainable cassava plant protection technologies for the most important arthropod, pathogen and weed pests in West Africa. Multi-disciplinary teams of national plant protection experts join regionally with international experts to share exrpetise and pool efforts across agroecologies. Project activities are divided into three interrelated and overlapping phases. The major cassava pests are being identified in targeted agroecologies through initial diagnostic surveys. In the second phase, farmers' participation highlights the development and testing of appropriate intervention technologies. Concurrently, in-service training of researchers, extension agents and farmers in the principles and practices of sustainable crop production and protection is provided. Postgraduate training will be provided to women to strengthen their professional resource base in plant protection development activities. The third phase is an evaluation of the training objectives and technology implementation. Unique features of the project include nationally seconded multi-disciplinary teams, shared local expertise on a regional basis and activities based on local diagnoses. The project is a collaborative effort between the International Institute of Tropical Agriculture (IITA), national plant protection staff, extension workers and farmers in Cameroon, Nigeria, Benin and Ghana, with a parallel component in Brazil involving Centro Internacional de Agricutura Tropical (CIAT) and Empresa Brasileira de Pesquisa Agropecüaria (EMBRAPA). The research, training, implementation and evaluation paradigm used in this project can serve as a model for developing appropriate plant protection technologies and pest management strategies for other cropping systems.